The evolution of molecular biology the search for the secrets of life - Van Holde, Kensal E; Zlatanova, J. (Elsevier, 2018)
"The Evolution of Molecular Biology: The Search for the Secrets of Life provides the historical knowledge behind techniques founded in molecular biology, also presenting an appreciation of how, and by whom, these discoveries were made. It deals with the evolution of intellectual concepts in the context of active research in an approachable language that accommodates readers from a variety of backgrounds. Each chapter contains a prologue and epilogue to create continuity and provide a complete framework of molecular biology. This foundational work also functions as a historical and conceptual supplement to many related courses in biochemistry, biology, chemistry, genetics and history of science. In addition, the book demonstrates how the roots of discovery and advances-and an individual's own research-have grown out of the history of the field, presenting a more complete understanding and context for scientific discovery"--Back cover.